2003
DOI: 10.1109/tip.2002.807582
|View full text |Cite
|
Sign up to set email alerts
|

Multiple motion segmentation with level sets

Abstract: Segmentation of motion in an image sequence is one of the most challenging problems in image processing, while at the same time one that finds numerous applications. To date, a wealth of approaches to motion segmentation have been proposed. Many of them suffer from the local nature of the models used. Global models, such as those based on Markov random fields, perform, in general, better. In this paper, we propose a new approach to motion segmentation that is based on a global model. The novelty of the approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…However, the spatial segmentation stage is often time consuming, and getting an effective improvement on the final motion segmentation accuracy remains questionable. Using the level-set framework is another way to precisely locate region boundaries while dealing with topology changes [38,39], but handling a competitive motion partioning of the image (with the number of regions a priori unknown) remains an open issue in that context even if recent attempts have been reported [11,26].…”
Section: Discrete Motion Labels and Motion Segmentationmentioning
confidence: 99%
“…However, the spatial segmentation stage is often time consuming, and getting an effective improvement on the final motion segmentation accuracy remains questionable. Using the level-set framework is another way to precisely locate region boundaries while dealing with topology changes [38,39], but handling a competitive motion partioning of the image (with the number of regions a priori unknown) remains an open issue in that context even if recent attempts have been reported [11,26].…”
Section: Discrete Motion Labels and Motion Segmentationmentioning
confidence: 99%
“…Most motion segmentation models are based on the estimation of optical flow, i.e., the 2D velocity of image points or regions, based on the variation of their intensity values. Mansouri and Konrad (2003) have employed optical flow estimation to segmentation with an active model. They propose a competition approach based on a level set representation.…”
mentioning
confidence: 99%
“…Furthermore energetic model does not well represent what occurs in occlusion areas. Labeling in such areas may then be quite random such as observed in [3].…”
Section: Short Term Energetic Modelmentioning
confidence: 99%
“…Many approaches have already been proposed to realize segmentation, such as motion detection with regularization constraints (e.g. Markov Random Fields) [1], region growing [2], or active contours [3,4]. In [5], it has been shown that most of those approaches can be unified as an energetic modeling problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation